ANALISIS PERUBAHAN PERENCANAAN PEMBANGUNAN EKONOMI INDONESIA PASCA PANDEMI COVID-19 - Suryana, Desi Fitriyani; Aisyah, Dara Istia; Maulana, Kenji (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2023)
AbstractIn the context of recovering the Indonesian economy after the pandemic covid 19, Of course, the government must prepare a plan for Indonesia's economic development. The Government of Indonesia has completed the preparation of the National Medium Term Development Plan (RPJMN) 2020 – 2024 during the pandemic Covid-19 began to spread throughout the world, as set forth in Presidential Regulation No. 18 of 2020 on February 14, 2020. Planning for Indonesia's economic development in the current period refers to the President's Vision and Mission, namely the Realization of an Advanced Indonesia that is Sovereign, Independent, and Has a Personality Based on Mutual Cooperation which is used as the main basis for preparing the 2020–2024 RPJMN, which will be translated hereinafter into the 7 development agendas. This study aims to find out how Indonesia's economic development planning has changed after the Covid-19 pandemic. This type of research is qualitative, with a literature review method or literature review that contains theories relevant to the topic studied.